Chromosome synapsis, recombination and epigenetic modification in rams heterozygous for metacentric chromosome 3 of the domestic sheep Ovis aries and acrocentric homologs of the argali Ovis ammon - T. I. Bikchurina; E. K. Tomgorova; A. A. Torgasheva; V. A. Bagirov; N. A. Volkova; P. M. Borodin (Вавиловский журнал генетики и селекции)
Hybridization of domestic animal breeds with their wild relatives is a promising method for increasing the genetic diversity of farm animals. Resource populations derived from the hybridization of various breeds of domestic sheep with mouflon and argali are an important source of breeding material. The karyotypes of argali and domestic sheep differ for a Robertsonian translocation, which occurred in the common ancestor of mouflon and domestic sheep (Ovis aries) due to the centric fusion of chromosomes 5 and 11 of the argali (O. ammon) into chromosome 3 of sheep. It is known that heterozygosity for translocation can lead to synapsis, recombination and chromosome segregation abnormalities in meiosis. Meiosis in the heterozygotes for translocation that distinguishes the karyotypes of sheep and argali has not yet been studied. We examined synapsis, recombination, and epigenetic modification of chromosomes involved in this rearrangement in heterozygous rams using immunolocalization of key proteins of meiosis. In the majority of cells, we observed complete synapsis between the sheep metacentric chromosome and two argali acrocentric chromosomes with the formation of a trivalent. In a small proportion of cells at the early pachytene stage we observed delayed synapsis in pericentromeric regions of the trivalent. Unpaired sites were subjected to epigenetic modification, namely histone H2A.X phosphorylation. However, by the end of the pachytene, these abnormalities had been completely eliminated. Asynapsis was replaced by a nonhomologous synapsis between the centromeric regions of the acrocentric chromosomes. By the end of the pachytene, the γH2A.X signal had been preserved only at the XY bivalent and was absent from the trivalent. The translocation trivalent did not differ from the normal bivalents of metacentric chromosomes for the number and distribution of recombination sites as well as for the degree of centromeric and crossover interference. Thus, we found that heterozygosity for the domestic sheep chromosome 3 and argali chromosomes 5 and 11 does not cause significant alterations in key processes of prophase I meiosis and, therefore, should not lead to a decrease in fertility of the offspring from interspecific sheep hybridization.